'POST-HIP': NEW MUSIC FOR OLD INSTRUMENTS IN THE TWENTY-FIRST CENTURY. (July 2021) - Tassie, Benjamin
Abstract: This article explores an emergent vanguard of the 'historically informed performance' (HIP) movement in the twenty-first century, focusing on new music written for, and performed on, historical instruments. Drawing on musicological and journalistic writing, as well as first-hand interviews with artists working in the scene, discussion is centred around the work of three key practitioners: the lutenist Jozef van Wissem, gambist Liam Byrne and baroque violinist Halla Steinunn Stefánsdóttir. Finally, an attempt is made to situate the scene, both in relation to earlier revivalist practice and to broader cultural trends, drawing, in particular, on notions of 'retromania', post-internet and post-postmodernist practice.